2005
DOI: 10.1242/dev.01936
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for endoderm and BMP signaling in sensory neurogenesis in zebrafish

Abstract: Cranial sensory neurons largely derive from neurogenic placodes(epibranchial and dorsolateral), which are ectodermal thickenings that form the sensory ganglia associated with cranial nerves, but the molecular mechanisms of placodal development are unclear. Here, we show that the pharyngeal endoderm induces epibranchial neurogenesis in zebrafish, and that BMP signaling plays a crucial role in this process. Using a her5:egfptransgenic line to follow endodermal movements in living embryos, we show that contact be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 58 publications
5
88
0
Order By: Relevance
“…We blocked RA signaling at different time points post-gastrulation between 16 -30 hpf. In untreated embryos, the first endodermal pouch appears to be fully formed at around 18 hpf (our data; Crump et al, 2004;Holzschuh et al, 2005), the second at approximately 22 hpf, the third at 24 hpf, the fourth at 28 hpf, and the fifth at 30 hpf. Application of DEAB between 20 -30 hpf results in an underdeveloped pouch 4 and pouch 5 is missing (Fig.…”
Section: Ra Signaling Is Required For Endodermal Pouch Morphogenesissupporting
confidence: 50%
“…We blocked RA signaling at different time points post-gastrulation between 16 -30 hpf. In untreated embryos, the first endodermal pouch appears to be fully formed at around 18 hpf (our data; Crump et al, 2004;Holzschuh et al, 2005), the second at approximately 22 hpf, the third at 24 hpf, the fourth at 28 hpf, and the fifth at 30 hpf. Application of DEAB between 20 -30 hpf results in an underdeveloped pouch 4 and pouch 5 is missing (Fig.…”
Section: Ra Signaling Is Required For Endodermal Pouch Morphogenesissupporting
confidence: 50%
“…Notably, pharyngeal segmentation time is roughly twice as long in tilapia as in zebrafish, 30 hr versus 14-16 hr (Fig. 13B) (Holzschuh et al, 2005), which parallels the overall slower embryonic development of tilapia relative to zebrafish (Fujimura and Okada, 2007). Although in vivo studies of zebrafish pouch formation have shown that the first and second pouch primordia consist of groups of six to ten cells (Holzschuh et al, 2005), our histological observations show a number of cells several orders of magnitude higher in tilapia pouch primordia (Fig.…”
Section: History Of a Key Evolutionary Innovationmentioning
confidence: 53%
“…The pharyngeal wall is subsequently compartmentalized by a series of six outpocketings of endoderm called pharyngeal pouches (pp). In contrast to the two preotic NC populations that are spatially distinct prior to the onset of pouch formation, a single mass of postotic NC cells becomes segmented into five distinct populations after migration (Kimmel et al, 2001;Holzschuh et al, 2005). To determine if a similar sequence of events characterizes pharyngeal development in tilapia, we performed histological sections at various stages of arch morphogenesis, and whole-mount in situ hybridization with tilapia orthologues of genes expressed in NC and pp in zebrafish.…”
Section: Pharyngeal Arch Segmentation In Nile Tilapia Embryosmentioning
confidence: 99%
“…In chick embryos, for example, Begbie et al (1999) demonstrated that Bmp7 is expressed in endodermal pouches at stage 13, at which neuroblasts start to delaminate and differentiate in embryos, and that it works as a potent inducer of epibranchial neurons in vitro. Two additional reports demonstrated a requirement for the endoderm-derived secreting molecules, FGF3 (Nechiporuk et al, 2005), BMP2b, and BMP5 (Holzschuh et al, 2005) for neurogenesis in the epibranchial ganglia in zebrafish. So far, however, no initial signal for the specification of the epibranchial placode has been identified.…”
Section: Fgf8 Is a Candidate Molecule For The Initial Specification Fmentioning
confidence: 99%
“…Begbie et al (1999) demonstrated that chick bone morphogenetic protein-7 (BMP7) is a signaling molecule that induces epibranchial placode-derived neurons. Endoderm-derived BMP2b/5 (Holzschuh et al, 2005) and FGF3 (Nechiporuk et al, 2005) were also shown to play crucial roles in epibranchial neurogenesis in zebrafish embryos.…”
Section: Introductionmentioning
confidence: 98%